e-SPRINT™ 4E – courseware on basic electricity - Ab. Aziz, Sidek; Azman, Siti Nor Azidah; Amat Hanim, Nur Aqila; Khairul Anuar, Noor Athirah; Zamani, Maisarah (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
The integration of multimedia in teaching and learning process to occur more attractive way in form of the multimedia courseware, The aim of this study is to develop computer-based learning courseware for the field of electricity by using Microsoft Power Point powered by iSpring Suite 8 technology as development platform. A pre-test survey was conducted to 50 physics students to identify and analyze their problems in the field of Electricity before courseware was developed. The main goal of the development of this courseware is meant to strengthen students' understanding of the theories and concepts taught in this field. eSPRINT™ 4E is a physics courseware exclusive package consists of basics of electricity such as electric charge and fields, electric potential, electromagnetic induction as well as capacitance and dielectric. In order to evaluate the multimedia courseware developed based on respondents' perception, a post-test survey was conducted to 100 respondents who has enrolled the Physics courses. Generally, the average respondents' perception towards the developed courseware was positive. This present study showed that most of the student prefer to learn in interactive way such as through the courseware which is more fun and flexible. To conclude, the overall items in the survey have been interpreted positively by the respondents. eSPRINT™ is a registered trade mark No. 0600499 Class : (41) in Malaysia 30/03/2006.